HUBUNGAN PRAKTIK PEMBERIAN MAKAN DAN PENDIDIKAN IBU TERHADAP PERILAKU PICKY EATER PADA ANAK PRA SEKOLAH - Mita Dwi Puspitasari; Listyaning Eko Martanti; Budi Astyandini (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
Perfect brain growth and development occurs when a child is 6 years old, therefore the success of brain growth and development is largely determined before the child is 6 years old. Pre-school children often experience picky eaters furthermore the picky eater is also the result of the play stage of the eating behavior of the closest people, especially the mother. The role of mothers is very influential because mothers have more free time with children, therefore the need for a good mother's role in terms of feeding practices. The purpose of this study was to determine the relationship between feeding practices on picky eater behavior in pre-school children. The sample used was 58 respondents who were selected using purposive sampling. This study was analyzed using the Chi Square test. The results showed that there was a significant relationship between feeding practices and picky eater behavior in pre-school children with the results showing a p value of 0.001 (0.05) and there was no significant relationship between mother's education and behavior. picky eaters in pre-school children aged 3-5 years with the results of the study showing a p value of 0.589 (0.05).